Disaster management - Harsh K.Gupta; Gupta, Harsh K. (Hyderabad : Universities Press : Distributed by Orient Longman, 2003)
With reference to India.
Vegetal cover and natural disaster management in Himalaya / P.S. Ramakrishnan -- The spacio-temporal aspects of monsoon floods in India : implications for flood hazard management / Vishwas S. Kale -- Monitoring and forecasting of tropical cyclones and their associated effects / S.R. Kalsi -- A new seismic hazard map for the Indian plate region under the global seismic hazard assessment programme / M. Ravi Kumar and S.C. Bhatia -- Major and great earthquakes in the Himalayan Region : an overview / H. Gupta -- Two great landslide tragedies of India / R.K. Bhandari -- Droughts / D.P. Rao.
Includes bibliographical references and index.
Keywords: Natural disasters -- India; Hazardous geographic environment -- India; Emergency management -- India